Optimizing The Snakes and Ladders Game as A Health Education Media for Premarital Couples at Puskesmas Cawas I, Klaten District - Helmi Nurlaili; Henik Istikhomah; Dewi Susilowati; Dev Raj Paneru (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Indonesia’s Maternal Mortality Rate is still high with the most common causes in 2023 were hypertension in pregnancy, obstetric hemorrhage, obstetric complications, and other causes. It reveals that before marriage, every individual needs to plan their pregnancy, including getting reproductive health services and reproductive health rights in order to improve health status through maternal health program interventions. Premarital couples are required to attend Premarital Class held by The Ministry of Religious Affairs, Ministry of Health, and the National Population and Family Planning Agency. The midwives provide information of reproductive health by lecturing method. The Snakes and Ladders game is expected to be capable of increasing participation of premarital couples actively so it can elevate their knowledge about reproductive health, pregnancy preparation, anemia, and CED. This community service activity was held on Sunday, March 2, 2025 at Puskesmas Cawas I, Klaten Regency. The tools were banners as game boards and dice. Additional information was conveyed orally with laptop and LCD. Premarital couples had to filling out pre and post questionnaire consist of 10 items. The premarital couples were enthusiastic during the game. Representatives of each group completed the game. Their partner involved by providing answers to the questions they got. Bivariate analysis using Paired T Test shows that ρ value < 0.05. It is concluded that education through Snakes and Ladders game is proven to enhance premarital couples' knowledge about reproductive health, pregnancy preparation, anemia, and CED.